Strategi Rebranding Guna Meningkatkan Brand Awareness: (Studi Kasus Revitalisasi Lokananta Sebagai Ruang Publik di Surakarta) - Puspitasari, Reza; Hindra Hastuti, Nurnawati; Mahar Rizqi, Fikriana (Solidaritas, 2024)
Previously, Lokananta was the first recording studio in Indonesia located in Solo City, but it has now transformed into a public space with an educational tourist destination. Following the revitalization process and a change in its business objectives, Lokananta Surakarta created a vision to become a Creative and Commercial Hub for local musicians, artists, and UMKMs, thereby contributing to social impact, economic growth, and the preservation of Indonesian culture. The aim of this study is to understand and describe the rebranding strategies employed by Lokananta after its revitalization to enhance brand awareness. This research uses a qualitative descriptive approach with a case study method to describe the issues and focus of the study. In executing its rebranding process, Lokananta employed several primary strategies, including: 1. Repositioning 2. Renaming 3. Redesigning, 4. Relaunching. Additionally, to maintain and enhance its brand awareness, Lokananta utilized strategies such as: publication, events, community building, informing or imaging, lobbying and negotiation, and social responsibility. The results show that Lokananta has successfully executed rebranding while maintaining its primary role as an Indonesian recording industry while providing valuable experiences for visitors. Keywords: Rebranding, Lokananta, public space, brand awareness